Prevalence of visual impairment among adults aged forty years and above in the MOH area Mahara - Hapugoda, H.T.C.J (My University, 2009)
Study population consisted of 602 adults aged forty years and above selected from applying cluster sampling technique. Study instruments were interviewer administered questioner and a record sheet.. Data analysis was done sing SPSS 16th version. Prevalence visual impairments and its 95 percent confidence intervals (CI ) were calculated. Multivariate logistic regression was applied for assessment of factors associated with cataract. Results were expressed as odds ratios and its 95 percent CIs. Visual impairment was a health problem among adults aged 40 years and above in the MOH area Mahara. Being an elderly, low income and longer duration of alcohol consumption were associated with cataract